2007
DOI: 10.1097/01.pap.0000249909.54047.0e
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Plus Low-Dose Glimeperide Significantly Improves Homeostasis Model Assessment for Insulin Resistance (HOMAIR) and β-Cell Function (HOMAβ-cell) Without Hyperinsulinemia in Patients With Type 2 Diabetes Mellitus

Abstract: Metformin plus low-dose glimepiride (plus ADA diet and physical activity) is a more effective treatment for type 2 diabetes than either metformin plus ADA diet and physical activity or ADA diet and physical activity alone. Determination of HOMA(IR) and HOMA(beta-cell) values is an inexpensive, reliable, less invasive, and less labor-intensive method than other tests to estimate insulin resistance and beta-cell function in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…The reduction in HOMA‐IR following metformin supplementation could be simply attributed to its effect on fasting insulin rather than fasting glucose concentration. The current result is in accord with Bermúdez‐Pirela et al () report, which showed the improvement of insulin resistance using metformin in combination with glimepiride on the fasting glucose level, HOMA‐IR, HOMA‐β, and glycosylated hemoglobin. Although metformin offered little benefit over vitamin D, and a combination therapy only showed successful improvements of insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in HOMA‐IR following metformin supplementation could be simply attributed to its effect on fasting insulin rather than fasting glucose concentration. The current result is in accord with Bermúdez‐Pirela et al () report, which showed the improvement of insulin resistance using metformin in combination with glimepiride on the fasting glucose level, HOMA‐IR, HOMA‐β, and glycosylated hemoglobin. Although metformin offered little benefit over vitamin D, and a combination therapy only showed successful improvements of insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…[34] The combined metformin and glimepiride (at low dose) is superior in the management of IR studied through HOMA with reduction in HOMA-IR. [35] Metformin is known to improve cardiopulmonary performance in patients with high HOMA-IR possibly by favorable effects on endothelial dysfunction. [18]…”
Section: Oral Treatmentmentioning
confidence: 99%
“…HOMA of insulin sensitivity and basal β -cell function are calculated as HOMA-IRI=FPG×fasting insulin (Fins)22.5, see [17]. Assume HOMA  β-cell  function(HOMA-β)=20×Fins(FPG3.5). …”
Section: Methodsmentioning
confidence: 99%